The Paradoxes of Telehealth: a Review of the Literature 2000–2015. (1st December 2016) - Standing, Craig; Standing, Susan; McDermott, Marie‐Louise; Gururajan, Raj; Kiani Mavi, Reza
Abstract : Telehealth literature has grown over the years to be a substantial body of work. However, research still highlights problems in extracting value from telehealth activities. In this paper, we analyse the telehealth literature over the period 2000–2015. The methodology focuses on paradoxes or surprises in the findings. We explain the lack of an operating model for telehealth as a debilitating feature of its history. We also note that many of the barriers cited in the literature have not changed over the period. We call for a focused research agenda on telehealth that provides clear evidence for some of the benefits such as cost savings and patient benefits. If telehealth activities are to progress, fundamental issues need to be addressed both in research and practice. Copyright © 2016 John Wiley & Sons, Ltd.